Jane Eyre - Berg, Maggie (Twayne Publishers, 1987)
Provides in-depth analysis of the literary work Jane Eyre, as well as its importance and critical reception. Includes a chronology of the life and works of the author
Description based on print version record
Keywords: Bronte; Charlotte; Jane Eyre; Autobiographical fiction; Governesses in literature; Women in literature; Self in literature